Predictive value of the triglyceride-glucose index for adverse clinical outcomes in chronic kidney disease - Lee, Jeong-Yeun; Jeong, Su Jin; Kim, Jin Sug; Jeong, Kyung Hwan; Hwang, Hyeon Seok (Frontiers in Endocrinology, 2026)
IntroductionThe triglyceride-glucose (TyG) index has been proposed as a reliable marker of insulin resistance. However, clinical significance of the TyG index in patients with chronic kidney disease (CKD) remains unclear.MethodsA total of 47,592 individuals with CKD who underwent nationwide health examinations between 2012 and 2015 were enrolled. Patients were classified into four quartiles based on their TyG index levels. The association between the TyG index and cardiovascular (CV) events, progression to end-stage kidney disease (ESKD), and all-cause mortality was evaluated.ResultsA higher TyG index was associated with an increased risk of CV events. Compared with patients in the lowest TyG index quartile, hazard ratios (HRs) and 95% confidence intervals (CIs) for CV events were 1.08 (1.00–1.17), 1.13 (1.04–1.22), and 1.39 (1.28–1.51) for the second, third, and fourth quartiles, respectively. The risk of progression to ESKD also increased with higher TyG quartiles, with adjusted HRs (95% CIs) of 1.22 (1.08–1.38), 1.35 (1.18–1.54), and 1.86 (1.65–2.10) across increasing TyG index quartiles. The risk of all-cause mortality was similarly elevated in patients in the highest TyG index quartile. Furthermore, the risks of ESKD progression and all-cause mortality across different levels of kidney function was more pronounced with increasing TyG index levels (all P for interaction< 0.001).ConclusionTyG index is a valuable predictor of CV event, progression to ESKD, and all-cause mortality in patients with CKD, and it significantly interacted with kidney function in relation to the risks of ESKD and mortality.